Implementasi Regulasi Berkendara di Bawah Umur Terhadap Keselamatan Jalan di Kabupaten Aceh Barat - Aufa, Ityan; Hajad, Vellayati (Public Administration Dept, Faculty of Social and Political Science, 2025)
This research investigates the issue of underage motorbike riding in West Aceh Regency, a pressing concern with significant implications for road safety and child health. The study aims to assess the implementation of Law No. 22 of 2009 on Traffic and Road Transport, focusing on its impact on reducing underage riders. Using Richard Matland's policy implementation theory as a framework, the study employs a qualitative case study approach. Data collection methods include observations, in-depth interviews with key stakeholders such as police officers, judicial figures, parents, and underage riders, alongside document analysis from relevant sources. The findings reveal that the enforcement of Law No. 22 of 2009 in curbing underage motorbike use remains ineffective. Key factors include the lack of awareness among both parents and children regarding the law’s importance and the minimal socialization efforts to promote it. Additionally, inadequate law enforcement and weak penalties contribute to this policy's limited success. The analysis also highlights the need for stronger outreach programs to educate the public on the risks of underage driving. In conclusion, the study emphasizes the necessity of intensifying law enforcement efforts, enhancing public education, and imposing stricter sanctions to foster compliance. By prioritizing these measures, the number of underage motorbike riders can be reduced, leading to improved road safety in West Aceh Regency.